2018
DOI: 10.1002/mus.26029
|View full text |Cite
|
Sign up to set email alerts
|

Nerve ultrasound in polyneuropathies

Abstract: Ultrasound can be used to visualize pathology in the peripheral nerves of patients with polyneuropathy. Nerve enlargement is the most frequent pathology, but other abnormalities, including abnormal nerve echogenicity and vascularity, are also encountered. This monograph presents an overview of the role of nerve ultrasound in the evaluation and management of both inherited and acquired polyneuropathies. A description of the sonographic techniques and common abnormalities is provided, followed by a presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 104 publications
(364 reference statements)
4
51
1
Order By: Relevance
“…This is somewhat different from the sonographic nerve appearance in patients with CIDP and MMN, in whom nerve enlargement tends to be more pronounced (up to 100% above the normal limit or even larger, especially in CIDP). Immune‐mediated neuropathies also present more asymmetric and regional CSA enlargement, which is especially the case in MMN . Sonographic differences and our careful diagnostic work‐up (discussed in Materials and Methods) convince us that the ALS subsample that was classified to have a state of PNS inflammation did not include LMN disease mimics such as CIDP or MMN.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This is somewhat different from the sonographic nerve appearance in patients with CIDP and MMN, in whom nerve enlargement tends to be more pronounced (up to 100% above the normal limit or even larger, especially in CIDP). Immune‐mediated neuropathies also present more asymmetric and regional CSA enlargement, which is especially the case in MMN . Sonographic differences and our careful diagnostic work‐up (discussed in Materials and Methods) convince us that the ALS subsample that was classified to have a state of PNS inflammation did not include LMN disease mimics such as CIDP or MMN.…”
Section: Discussionmentioning
confidence: 86%
“…Immune-mediated neuropathies also present more asymmetric and regional CSA enlargement, which is especially the case in MMN. 9 Sonographic differences and our careful diagnostic work-up (discussed in Materials and Methods) convince us that the ALS subsample that was classified to have a state of PNS inflammation did not include LMN disease mimics such as CIDP or MMN.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A recent study has shown that nerves are on average slightly enlarged compared to healthy subjects in patients with DM [18]. Nerve enlargement has been found in other neuropathies such as hereditary neuropathies like POEMS or metachromatic leukodystrophy or acquired conditions such as leprosy or sarcoidosis [19]. WFR is, among others, a widely used method to sonographically support the diagnosis of CTS or even exclude the necessity for surgical repair and thus triages patients.…”
Section: Introductionmentioning
confidence: 99%